Liver cirrhosis may increase the incidence of delayed bleeding and mortality after endoscopic retrograde cholangiopancreatography for common bile duct stones - Li, Linzhen; Wang, Di; Niu, Xiaoping (Frontiers in Medicine, 2025)
Background and purposeCholedocholithiasis is a common disease. However, the results of studies on the complications of choledocholithiasis with cirrhosis by endoscopic retrograde cholangiopancreatography (ERCP) are inconsistent. Therefore, the purpose of this prospective study is to compare the incidence of postoperative complications of ERCP between choledocholithiasis with cirrhosis and those without cirrhosis.Patients and methodsA total of 259 choledocholithiasis patients were include in this study. According to whether the choledocholithiasis patients were complicated with cirrhosis, they were divided into cirrhosis group and non-cirrhosis group. The incidence of post-ERCP pancreatitis (PEP), delayed bleeding, infection, perforation, and mortality were compared between the two groups.ResultsThere were 34 choledocholithiasis patients with cirrhosis and 225 patients without cirrhosis. There were statistically significant differences in delayed hemorrhage (p = 0.046) and mortality (p = 0.017) between the two groups. The rate of delayed hemorrhage and mortality in choledocholithiasis with cirrhosis patients group were significantly higher than those without cirrhosis. There were no statistically significant differences in PEP (p = 0.917), postoperative biliary tract infection (p = 0.130), stone clearance (p = 0.201), and perforation (p = 1.000) between the two groups.ConclusionThe results of this study found that cirrhosis may be associated with the occurrence of ERCP complications. Delayed hemorrhage and mortality after ERCP in choledocholithiasis patients with cirrhosis were significantly higher than those without cirrhosis.